Gralen, kætterne og korstoget – Myter og middelalderisme i Languedoc - Imer Kappel, Trine (Slagmark - Tidsskrift for idéhistorie, 2019)
The Languedoc region between the Rh.ne River and the Pyrenees is renowned for its medieval history. Or rather, its special version of medievalism. This article seeks to explain how and why the Albigensian Crusade (1209-1229) and the heretical Cathars came to be intertwined with myths about the Holy Grail after World War I by examining three different definitions of medievalism by Eco, Gentry & Müller, and Matthews. The theories approach medievalisms from different perspectives, but they all pay special attention to the political usage of medievalisms, which can be detected in all corners of the Albigensian Crusade historiography and fictional literature. This shows that a special Occitanian medievalism-hybrid has been created, which is constantly being developed and highlighted by both literature, myths and the region’s tourism industry. Finally, the article argues that the perceptions of medieval Languedoc and the myths surrounding the area reflects the challenges and political reality of the authors’ own time and experiences.